One night of total sleep deprivation promotes a state of generalized hyperalgesia: A surrogate pain model to study the relationship of insomnia and pain - Schuh-Hofer, Sigrid; Wodarski, Rachel; Pfau, Doreen B.; Caspani, Ombretta; Magerl, Walter; Kennedy, Jeffrey D.; Treede, Rolf-Detlef (Pain (Amsterdam), 2013)
One night of total sleep deprivation results in generalized hyperalgesia and mood changes. TSD emerges a translational surrogate pain model for studies on the relationship between insomnia and pain. Sleep disturbances are highly prevalent in chronic pain patients. Understanding their relationship has become an important research topic since poor sleep and pain are assumed to closely interact. To date, human experimental studies exploring the impact of sleep disruption/deprivation on pain perception have yielded conflicting results. This inconsistency may be due to the large heterogeneity of study populations and study protocols previously used. In addition, none of the previous studies investigated the entire spectrum of nociceptive modalities. To address these shortcomings, a standardized comprehensive quantitative sensory protocol was used in order to compare the somatosensory profile of 14 healthy subjects (6 female, 8 male, 23.5±4.1year; mean±SD) after a night of total sleep deprivation (TSD) and a night of habitual sleep in a cross-over design. One night of TSD significantly increased the level of sleepiness (P<0.001) and resulted in higher scores of the State Anxiety Inventory (P<0.01). In addition to previously reported hyperalgesia to heat (P<0.05) and blunt pressure (P<0.05), study participants developed hyperalgesia to cold (P<0.01) and increased mechanical pain sensitivity to pinprick stimuli (P<0.05) but no changes in temporal summation. Paradoxical heat sensations or dynamic mechanical allodynia were absent. TSD selectively modulated nociception, since detection thresholds of non-nociceptive modalities remained unchanged. Our findings show that a single night of TSD is able to induce generalized hyperalgesia and to increase State Anxiety scores. In the future, TSD may serve as a translational pain model to elucidate the pathomechanisms underlying the hyperalgesic effect of sleep disturbances.